Deciphering the association networks of mycobiome communities among the elderly Danes - Hajar Fauzan, Ahmad; Faust, Karoline; Castro Mejia, Josue Leonardo; Kot, Witold; Bechshøft, Rasmus; Reitelseder, Søren; Holm, Lars; Nielsen, Dennis Sandris (2017)
Changes of microbial communities have been linked to frailty in elderly, yet the presence of fungal communities and their associations are little understood. This study attemps to identify biologically meaningful gut microbial fungal associations during aging. Faecal samples of 100 Danes of 65 years or older were collected, and sequenced by high-throughput tag-encoded sequencing of ITS2 gene fragments. The sequences were analysed using QIIME and CoNet to characterise fungal communities, and generate association networks, respectively. HbA1c, identified as the principal node, was grouped into 3 clusters based on glycated glucose levels. The clusters correspond to the phyla Ascomycota, Basidiomycota and Zygomycota, with the genera Penicillium, Candida, and Aspergillus being particularly abundant within each cluster. Interestingly, Bray-Curtis dissimilarity matrices showed significant (P<0.05) variation between clusters. These findings suggest that the presences of specific gut mycobiome members are associated with glycemic behaviours among the healthy individuals of the elderly Danish population.